Reduction of apparent water losses - Rimeika, Mindaugas; Albrektienė, Ramunė (International Conference “Environmental Engineering”, 2017)
The water loss levels are very different between European countries as water loss varies from 7% to 50%. According to data from the Lithuanian Water Supply Association, in 2015 about 124 mln. m³ of ground water was supplied to the network, but only 94 mln. m³ of it was sold, while the remaining share represented water losses – 30 mln. m³ per year. An average water loss level in Lithuania is 24%, varying from 52% to 17%. Local water utilities take a little care of apparent water losses. This article deals with an investigation of apparent losses in Alytus and other cities in Lithuania. The reduction of apparent water losses is quite a different field as it does not require large additional investments and can produce quick and efficient results. Article presents the results on the ways for reduction of apparent water losses in Lithuanian water supply systems. The aim of research is to show that apparent water losses consist of considerable share of water losses and to prove that inconsiderable efforts can significantly cut down water losses and improve the utilities’ financial situation. Article present findings of night water consumption, used for DMA allowed minimum water calculation. Analysing water consumption data in blockhouses the minimum night water volume was determined (0.9 l/h/flat).